2015
DOI: 10.1007/s00467-015-3105-7
|View full text |Cite
|
Sign up to set email alerts
|

Ibuprofen-associated acute kidney injury in dehydrated children with acute gastroenteritis

Abstract: Ibuprofen-associated AKI was 54 % in our cohort of dehydrated children with AGE. Drug exposure increased the risk for developing AKI by more than twofold, independent of the magnitude of the dehydration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
2
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 27 publications
3
50
2
2
Order By: Relevance
“…The children who developed acute renal injury tended to be younger (0.66 vs. 1.74 years; p  < 0.001) and had more frequently taken ibuprofen (74 vs. 49%, p  = 0.01). The authors emphasised that children under 6 months old have a higher risk of ibuprofen-related renal toxicity [8]. …”
Section: Safety and Tolerability Of Ibuprofenmentioning
confidence: 99%
See 1 more Smart Citation
“…The children who developed acute renal injury tended to be younger (0.66 vs. 1.74 years; p  < 0.001) and had more frequently taken ibuprofen (74 vs. 49%, p  = 0.01). The authors emphasised that children under 6 months old have a higher risk of ibuprofen-related renal toxicity [8]. …”
Section: Safety and Tolerability Of Ibuprofenmentioning
confidence: 99%
“…Emerging research has shown that the main side effects of ibuprofen involve the gastrointestinal system [7] and the kidneys [8], especially in feverish dehydrated individuals.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, NSAID use is common in children with SCD [30], without evidence to support its benefit compared to other less nephrotoxic options [31]. Similarly, the use of NSAIDS in children hospitalized for various other reasons, including dehydration due to gastroenteritis, was associated with a significant increase in the incidence of AKI [32,33]. Therefore, it is not surprising that hemodynamic-mediated AKI secondary to NSAIDs, a potential modifiable risk factor, is relatively common in this population, especially as SCD patients are often at higher risk of volume depletion at the time of presentation due to their inherent reduced urine concentrating ability.…”
Section: Sickle Cell Nephropathy and Akimentioning
confidence: 99%
“…The recommendation for NSAIDs during pain crisis is based on low quality evidence and does not provide any specific guidance on contraindications to NSAIDs [19]. The frequent administration of NSAIDs during prolonged pain crises likely places patients at increased risk for nephrotoxicity and AKI due to the underlying relative dehydration from hyposthenuria that SCD patients develop over time [21–23]. …”
Section: Introductionmentioning
confidence: 99%